2018
DOI: 10.1021/acs.inorgchem.8b01539
|View full text |Cite
|
Sign up to set email alerts
|

Doped Sr2FeIrO6—Phase Separation and a Jeff ≠ 0 State for Ir5+

Abstract: High-resolution synchrotron X-ray and neutron powder diffraction data demonstrate that, in contrast to recent reports, SrFeIrO adopts an I1̅ symmetry double perovskite structure with an abc tilting distortion. This distorted structure does not tolerate cation substitution, with low levels of A-site (Ca, Ba, La) or Fe-site (Ga) substitution leading to separation into two phases: a stoichiometric I1̅ phase and a cation-substituted, P2/ n symmetry, aac distorted double perovskite phase. Magnetization, neutron dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…The crystal structures used for the calculations correspond to the experimental room temperature crystal structures reported in the literature [8,9,16,17,36,39]. In the literature, it is also reported that no significant crystal structure changes occur at low temperature.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…The crystal structures used for the calculations correspond to the experimental room temperature crystal structures reported in the literature [8,9,16,17,36,39]. In the literature, it is also reported that no significant crystal structure changes occur at low temperature.…”
Section: Methodssupporting
confidence: 57%
“…Single crystals of Ba 2 YIrO 6 , Sr 2 YIrO 6 , and Bi 2 NaIrO 6 and polycristalline samples of Sr 2 FeIrO 6 , and SrLaBIrO 6 with B=(Ni, Zn) were grown following the procedures as described in the literature [8,9,16,17,36].…”
Section: Methodsmentioning
confidence: 99%
“…The triclinic symmetry of LaReN 3 is surprising given that the Goldschmidt tolerance factor t =0.99 based on Shannon ionic radii [27] is very close to the t =1 value for an ideal cubic perovskite. Observation of this small triclinic distortion provides indirect evidence that LaReN 3 is essentially stoichiometric, as small deviations in composition are known to increase symmetry to monoclinic as in other triclinic I true1 perovskites such as cation‐ordered Sr 2 FeIrO 6 [28] …”
Section: Figurementioning
confidence: 99%
“…Observation of this small triclinic distortion provides indirect evidence that LaReN 3 is essentially stoichiometric, as small deviations in composition are known to increase symmetry to monoclinic as in other triclinic I1 perovskites such as cation-ordered Sr 2 FeIrO 6 . [28] The ReÀN distances (Table 1) reveal that the ReN 6 octahedra are tetragonally elongated. Jahn-Teller distortion of t 2g 1 systems leads to tetragonal compression but for large spin-orbit coupling, as can be expected for Re VI , compression and elongation distortions become comparable in energy, as observed in A 2 TaCl 6 (A = K, Rb, Cs).…”
mentioning
confidence: 99%
“…Furthermore 5d metals experience much stronger spin orbit coupling (SOC) than 3d systems, so as a result the on-site coulombic repulsions (U), crystal field effects (Δ) and SOC interactions (λ) can be of comparable magnitude. This equivalence of energy scales can lead to unexpected behaviour, such as the antiferromagnetic insulating ground state of Sr2IrO4, 2 which can be attributed to strong SOC dividing the broad t2g 5 band (derived from the Ir 5d orbitals) into a filled quartet J = 3 /2 band and a half-filled doublet J = ½ band, the latter of which is sufficiently narrow that a Mott gap can be opened by small coulombic repulsions (U). A further feature arising from the similarity of the energy scales of U, Δ and λ is that small changes to any one of these interactions can lead to significant changes to the electronic and magnetic behaviour of 5d oxides systems.…”
Section: Introductionmentioning
confidence: 99%